2009
DOI: 10.1007/s00405-009-1155-9
|View full text |Cite
|
Sign up to set email alerts
|

A 3-year study of supraomohyoid neck dissection and modified radical neck dissection type I in oral cancer: with special reference to involvement of level IV node metastasis

Abstract: The present study was undertaken to determine the pattern and incidence of predictable lymphatic spread and skip metastasis in oral cancer and analyze the prognostic implications of different therapeutic modalities in the neck metastases. The study includes 81 patients with squamous cell carcinoma of oral cavity with T1-2N0M0 and T1-3N1-3M0 who were admitted to the Department of ENT and Head and Neck Surgery, SMS Medical College and Hospital, Jaipur, from June 2006 to May 2008. After complete diagnostic evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…In some reports, the incidence of level IV metastases is as high as 15%, which may justify routine dissection of this level . However, there are other reports demonstrating a low incidence of metastases in level IV . It is noteworthy that a significant proportion of neck recurrences occur because of skip metastases to levels III or IV, which is a finding that may support inclusion of level IV for prevention of neck recurrences.…”
Section: Introductionmentioning
confidence: 99%
“…In some reports, the incidence of level IV metastases is as high as 15%, which may justify routine dissection of this level . However, there are other reports demonstrating a low incidence of metastases in level IV . It is noteworthy that a significant proportion of neck recurrences occur because of skip metastases to levels III or IV, which is a finding that may support inclusion of level IV for prevention of neck recurrences.…”
Section: Introductionmentioning
confidence: 99%
“…Oral SCC is disseminated preferentially by the lymphatic system and mainly the cervical lymph nodes at levels I and II are affected ( 6 8 ). The high incidence of occult cervical lymph node metastases of ~25% in N0 cases in the clinic underscores the clinical significance and the resulting therapeutic difficulties ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Woolgar (Woolgar, 2006) demonstrated that an important proportion of neck recurrences occurred because of skip metastases to levels III or IV, which is a finding that supports extended supraomohyoid neck dissection for prevention of neck recurrences. On the other hand, there are various reports that demonstrate a low incidence of metastases in level IV (Mishra, 2010, Bajwa 2011. These authors have concluded that extension of dissection to include level IV did not offer an advantage for prevention of neck recurrences and level I-III dissection should be the preferred surgical procedure for management of clinically N0 oral cavity cancer (Bajwa, 2011).…”
Section: Extent Of Surgical Removal For Selective Neck Dissectionmentioning
confidence: 99%